Exploring different technological platforms for supporting co-located collaborative games in the classroom - Echeverría, Alejandro; Améstica, Matías; Gil, Francisca; Nussbaum, Miguel; Barrios, Enrique; Leclerc, Sandra (Computers in Human Behavior, 2012)
Abstract: Computer Supported Collaborative Learning is a pedagogical approach that can be used for deploying educational games in the classroom. However, there is no clear understanding as to which technological platforms are better suited for deploying co-located collaborative games, nor the general affordances that are required. In this work we explore two different technological platforms for developing collaborative games in the classroom: one based on augmented reality technology and the other based on multiple-mice technology. In both cases, the same game was introduced to teach electrostatics and the results were compared experimentally using a real class. The results of our experimental work showed that students significantly increased their conceptual understanding of electrostatics with both platforms. However, there were some important differences between platforms. While in the multiple-mice platform there were no gender differences, in the augmented reality platform boys significantly outperformed girls. In addition, the augmented reality platform was considerably more costly to deploy in a real world setting than the multiple-mice platform. These results suggest that, when co-located collaborative games are designed, careful consideration must be taken when selecting the technology to be used, something which can have effects that go beyond the effects of the games themselves.